Anesthesia and Outcome of 33 Surgeries in 24 Multiple Endocrine Neoplasia Type 2A (MEN2A) Patients: A National Rare Disease Center’s Experience - Li, Yaohan; Jin, Di; Shen, Le; Huang, Yuguang (Frontiers in Endocrinology, 2022)
Background Multiple endocrine neoplasia type 2A (MEN2A) is a rare syndrome that presents as medullary thyroid carcinoma, pheochromocytoma, and hyperparathyroidism. Experience is lacking in the anesthetic management of patients with this syndrome, particularly in those who present with pheochromocytoma receiving nonpheochromocytoma resection. We aimed to share our experience with the anesthetic management of MEN2A patients. Method We retrospectively enrolled 24 MEN2A patients who had received different types of surgery at Peking Union Medical College Hospital from January 1, 2015, to December 31, 2021. All the medical records were reviewed and analyzed. Result In total, 33 surgeries were performed in 24 MEN2A patients, with 20 surgeries comprising pheochromocytoma resection in 17 patients. Most of these patients who had received pheochromocytoma resection had typical hemodynamic changes during surgery and anesthesia. Regarding the other 13 nonpheochromocytoma resections in 13 patients, 10 were performed in patients without pheochromocytoma, and 3 surgeries were performed with either functional primary (1, bilateral tumor whose patient refused adrenalectomy) or metastatic pheochromocytoma (2, unresectable and malign tumors developed years after bilateral adrenalectomy). Regarding the latter 3 patients, 1 showed hypertension and tachycardia during anesthesia induction, 1 showed tachycardia during surgery and the other showed stability during surgery. Patients who had received pheochromocytoma resection (n=17) required longer postoperative hospital stays than those who had received nonpheochromocytoma resection without pheochromocytoma (n=10) (5.8 ± 1.8 vs. 4.3 ± 1.6; P = 0.031). Conclusions Whenever MEN2A patients are diagnosed with pheochromocytoma, surgical resection of the pheochromocytoma remains the primary choice for MEN2A treatment. Nonpheochromocytoma surgeries performed with existing pheochromocytoma could be risky and require full caution and preparation.